2006
DOI: 10.1111/j.1464-5491.2006.01867.x
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of oestrogens on postprandial lipid metabolism are lost in post‐menopausal women with Type 2 diabetes

Abstract: The oestrogen-associated advantage in clearance of dietary lipid we observed in non-diabetic post-menopausal women is not seen in post-menopausal diabetic women. This is likely to promote an atherogenic lipoprotein profile and may contribute to the loss of CVD protection seen in diabetic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…There was no significant difference in survival between the two genders in our data, which conflicts with previously reported all‐age population data; this likely reflects the older Medicare patient population that we analyzed. Postmenopausal women have been shown to lose health advantages in multiple areas over men once they reach this age bracket . Our data confirms both prior sinonasal cancer studies' findings of racial disparity in survival …”
Section: Discussionsupporting
confidence: 88%
“…There was no significant difference in survival between the two genders in our data, which conflicts with previously reported all‐age population data; this likely reflects the older Medicare patient population that we analyzed. Postmenopausal women have been shown to lose health advantages in multiple areas over men once they reach this age bracket . Our data confirms both prior sinonasal cancer studies' findings of racial disparity in survival …”
Section: Discussionsupporting
confidence: 88%
“…Postmenopausal women with heterozygous FH exhibit abnormal postprandial TG response compared with premenopausal FH women 35 . Postmenopausal estrogen therapy enhances the clearance of chylomicrons and chylomicron remnants 36 , but this beneficial effect is not observed in post-menopausal diabetic women 37 . In subjects with normal fasting TG levels, the postprandial concentration of chylomicron remnants is higher in normolipidemic women with CAD compared with matched controls without CAD 33 .…”
Section: Gender Menopausal Statusmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that the presence of postprandial hypertriglyceridemia poses an independent risk for coronary atherosclerosis [17]. Furthermore, the efficiency with which the body manages incoming dietary lipid can modulate disease risk in other chronic conditions such as obesity [8], type 2 diabetes [9,10], and non-alcoholic fatty liver disease, NAFLD [11]. Indeed, if poor metabolism of dietary triglyceride (TG) leads to ectopic lipid deposition, postprandial events may contribute more to disease development than currently appreciated.…”
Section: Introductionmentioning
confidence: 99%